2019
DOI: 10.14744/etd.2019.88557
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytology in pleural effusion: a single-center experience

Abstract: Objective: As a fast and effective method, cytopathological examination of the pleural fluid is the diagnostic tool of choice in determining the etiology of a spectrum of inflammatory to neoplastic conditions. The aim of the present study was to investigate the role of pleural cytology samples examined within a certain time period in determining the presence of malignant cells. Materials and Methods: Cytological materials of 433 patients with pleural effusion (PE) were retrospectively analyzed. Clinical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The database search yielded 3732 studies for screening with 181 potential studies identified for analysis. After full-text analysis, a total of 36 studies met inclusion criteria 2 3 7–40. A summary of the literature search is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The database search yielded 3732 studies for screening with 181 potential studies identified for analysis. After full-text analysis, a total of 36 studies met inclusion criteria 2 3 7–40. A summary of the literature search is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%